THE EFFECTIVENESS OF GLASSER LEARNING MODEL ON SPEAKING SKILLS (SPRECHFERTIGKEIT) IN GERMAN LANGUAGE EDUCATION STUDY PROGRAM STUDENTS UHKBPNP - Simanjuntak, Tarida Alvina; Purba, Lydia (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This study aims to improve the learning outcomes of students' speaking skills through an innovative learning model, namely by using Glasser's learning model. Speaking skills require learners to think creatively and innovatively. Speaking skills in German (Sprechfertigkeit) include linguistic materials and also discuss various forms of conversation/dialogue themes in accordance with themes that intersect with everyday life. Speaking skills are one of the four language skills that need to be instilled so that the communicative abilities of students can be developed optimally. This research was conducted by the German Language Education Study Program at Nommensen HKBP University Pematang Siantar. In this study using experimental method by using initial test and final text. This research procedure was carried out using a quasi experimental design because in this study there were external variables that could not be controlled by the researcher. The subjects of this study were all students of the German Language Education Study Program Semester 3 (three) Nommensen HKBP University Pematang Siantar Academic Year 2023/2024. With data collection techniques is to test the learning outcomes in accordance with the teaching material on learning speaking skills (Sprechfertigkeit). The results of this study indicate that the speaking ability of students by using the Glasser model increases than before. The difference can be seen from the results of data analysis on the pretest, which before the application reached an average of 54.61 classified as a poor category and the results of data analysis on the posttest, which after the application reached an average of 74.44 classified as a good category with a mean difference (D) Ì…) of -19.83. So it can be concluded that the Glasser learning model is proven effective in improving students' speaking skills.